Peran generasi muda dalam membangun budaya anti korupsi di Indonesia - Purwaningsih, Dewi (Maliki Interdisciplinary Journal, 2026)
Corruption is still one of the major problems in Indonesia because it affects national development, public welfare, and people’s trust in the government. Efforts to fight corruption cannot rely only on law enforcement, but also need to build an anti-corruption culture from an early age. In this case, young people have an important role as agents of change who can promote values such as honesty, responsibility, discipline, and concern for the public interest. This study aims to analyze the role of the younger generation in building an anti-corruption culture in Indonesia and to identify the forms of contribution they can make in everyday life. The method used in this study is a qualitative descriptive approach through literature review from journals, books, scientific articles, and data from related institutions. The results show that young people can contribute through character education, the use of social media as a tool for public education, participation in organizations, and the practice of honesty and transparency in schools and society. In addition, anti-corruption education from an early age is considered important to develop awareness and integrity in social life. Therefore, the role of the younger generation is very important in creating a cleaner, more honest, and corruption-free society in the future.